Sosialisasi Imunisasi Human Papillomavirus (HPV) dan Pemeriksaan Kesehatan Gratis sebagai Upaya Pencegahan Kanker Serviks pada Peserta Putri di SMP Al-Ma’ruf Kudus - Dian Arsanti Palupi; Yulia Pratiwi; Dwi Susiloningrum; Lilis Sugiarti; Darini Darini (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2026)
Human papillomavirus (HPV) is a common virus that infects the skin and is transmitted primarily through sexual contact. This virus can cause a variety of health problems, from common warts to serious cancers such as cervical, anal, penile, and throat cancer. Young women's knowledge and attitudes about cervical cancer have a significant and positive relationship with their motivation to receive the HPV vaccination. This outreach activity aimed to educate students about the importance of immunization in preventing infectious diseases like HPV in adolescents aged 9-14 years. This initiative aimed to prevent Human Papillomavirus infection, which can lead to cervical cancer, among others. Free health checks were also provided to detect potential health problems among students, such as vision problems, dental hygiene, nutritional status, blood pressure, and blood sugar levels. The students were enthusiastic about participating in this activity. Several students expressed their appreciation for being able to directly assess their health status and receive useful health education.